1988
DOI: 10.1111/j.1439-037x.1988.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Crop Rotation with an Increasing Content of Cereals on Photosynthetic Potential of Winter Wheat

Abstract: In years 1982–1985 flag leaf area, concentration of chlorophyll and macronutrients (N, P, K, Ca, Mg, Na) and also their correlations to grain yield in static field experiment were studied. The main experimental plots comprised crop rotations containing 50, 75, 100% cereals. Treatments with or without irrigation were subplots and nitrogen levels (0, 60, 120, 180 kg N/ha) were sub‐sub‐plots. The cultivation of winter wheat in rotations containing more than 50% cereals affected the drop of winter wheat grain yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…At this particular stage, the most decisive nutritional factor in determining the grain yield was the K concentration of the flag and third leaves. It is well documented that the flag leaf is important for covering grain-development requirements by assimilate production (Akmal et al, 2000;Grzebisz, 1988, Inoue et al, 2004Xu and Yu, 2006). The reported importance of the third leaf in yield determination emerged only under stress conditions as noted by Grzebisz et al (2009).…”
Section: Wheatmentioning
confidence: 93%
“…At this particular stage, the most decisive nutritional factor in determining the grain yield was the K concentration of the flag and third leaves. It is well documented that the flag leaf is important for covering grain-development requirements by assimilate production (Akmal et al, 2000;Grzebisz, 1988, Inoue et al, 2004Xu and Yu, 2006). The reported importance of the third leaf in yield determination emerged only under stress conditions as noted by Grzebisz et al (2009).…”
Section: Wheatmentioning
confidence: 93%
“…The same pattern has been observed for high-yielding rice [ 72 ]. The effective production of maize depends on the supply of K and N during the period preceding flowering, but requires stabilization of K accumulation up the milk stage [ 73 ]. It can be concluded that the high yield of the seed crops can be achieved, provided that the K:N ratio is higher than 1.0 during the vegetative phases for seed plant growth.…”
Section: Nitrogen-supporting Nutrientsmentioning
confidence: 99%
“…Stands that produced numerous shoots in fall and did not sustain losses in winter should not be supplied with very high N rates in early spring. Excess supply of N in spring can damage emerging shoots, and increased competition between tillers will inhibit the development of the root system [42]. In turn, winter wheat stands with sparse tillers require higher N rates in early spring [43].…”
Section: Introductionmentioning
confidence: 99%
“…Excess N supply in this period can lead to the rapid growth of above-ground biomass and tillers, which can contribute to lodging [43]. In many European regions, a third application of N in spring (BBCH [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] is required in the production of winter wheat for human consumption [34,35]. The third application of N enhances the quality of winter wheat by increasing the protein and gluten content of grain, but it has a minor effect on grain yield [43].…”
Section: Introductionmentioning
confidence: 99%